2018
DOI: 10.17269/s41997-018-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal heat response plan: evaluation of its implementation towards healthcare professionals and vulnerable populations

Abstract: The framework proposed in this study revealed valuable information that can be useful to improve plans aimed at reducing heat-related health effects in the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…These clients receive intensified interventions for health protection during heat events, such as more frequent phone calls and visits to check on well-being and uptake of preventive advice (Price et al 2013). In a follow-up assessment of the MHRP, data collated from reports, questionnaires, and focus groups found that increased contact with vulnerable clients was the most widely implemented recommendation, but that annual updating of vulnerability lists was the most widely cited challenge (Price et al 2018).…”
Section: Social Connection As Intervention During Extreme Heat Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…These clients receive intensified interventions for health protection during heat events, such as more frequent phone calls and visits to check on well-being and uptake of preventive advice (Price et al 2013). In a follow-up assessment of the MHRP, data collated from reports, questionnaires, and focus groups found that increased contact with vulnerable clients was the most widely implemented recommendation, but that annual updating of vulnerability lists was the most widely cited challenge (Price et al 2018).…”
Section: Social Connection As Intervention During Extreme Heat Eventsmentioning
confidence: 99%
“…The guidelines include place-based interventions to address the intersection of heat and isolation, such as the establishment of a common “chill room” where residents can seek refuge while engaging socially with others. Enhanced social activity in air-conditioned spaces would address one of the major challenges identified by the MHRP review (Price et al 2018 ), and could also improve use of public cooling shelters by vulnerable individuals (Sampson et al 2013 ).…”
Section: Social Connection As Intervention During Extreme Heat Eventsmentioning
confidence: 99%
“…Altogether, 620 articles underwent further abstract screening and 30 articles were selected for full-text screening. Of these, one study examined nursing home residents only [31]; one study did not fulfil the minimum age limit of 65 [32]; one article discussed heat susceptibility and health promotion in general but did not conduct any studies or evaluation [33]; one study discussed health promotion but not related to heat health [34]; three studies assessed mortality/morbidity rates related to heat but not against any components of heat action plans [35,36,37]; five articles were not assessing heat health and/or older people specifically [38,39,40,41,42]—all twelve were excluded. A total of 18 articles remained for analysis (See Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…As part of a heat warning system, these measures could reduce complications and mortality on hot days. [ 64 65 ]…”
Section: Discussionmentioning
confidence: 99%